The role of plastidial transporters in developing embryos of oilseed rape (Brassica napus L.) for fatty acid synthesis. (December 2000) - Kubis, S. E.; Rawsthorne, S.
Abstract : The phosphoenolpyruvate transporter (PPT) is one of several important transporters for channelling carbon intermediates utilized for fatty acid synthesis and other plastidial pathways from the cytosol into the plastid. In this paper we show results on how the activity of the PPT changes between two important, physiologically different developmental stages of oilseed rape embryos.